Survey Kualitas Pelayanan Posyandu Balita di Desa Majasem, Kecamatan Kendal, Kabupaten Ngawi - Mufida Aziza Baroroh; Heru Santoso Wahito Nugroho; Ayesha Hendriana Ngestiningrum (Gema Bidan Indonesia, 2021)
Posyandu is the role of the community, which organizes a system services to fulfill basic needs, improve human quality, empirically has been able to equalize services in the health sector. The utilization rate of posyandu services by the community especially to maternal is still not running optimally. This is show by the number of Posyandu visits that have not reach 70% target of Ngawi Regency. Therefore, researcher wanted to conduct a Quality Survey for child Posyandu Services. This research type is descriptive. The sample was 220 maternal. This research used Simple Random Sampling techniques. The instrument of this research closed questionnaire filled by respondents. The research only uses a single variable that’s Quality of child Posyandu Services. The results of the study shown that almost every attribute Quality of child posyandu services based on the leve l of importance and performance in relatively encouraging posyandu patients. Priority attributes include posyandu places, availability of toilets, consultation with officers (cadres or midwivery), officers in measuring height quickly and precisely and subsequent posyandu schedule information. Keywords: quality; attributes; posyandu.